PENGARUH PELATIHAN, IKLIM ORGANISASI DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PEGAWAI DINAS KESEHATAN KOTA TANJUNGBALAI - Novi Sriana; Sri Mulyani Rahimah; Agung Hasan Sadikin; Ferdinan Pendiangan; Riccy Sauty (Manajemen dan Bisnis, 2021)
The formulation of the problem in this study are: How the influence of training, organizational climate and work environment on the work performance at Dinas Kesehatan Kota Tanjungbalai. This study aims to determine the effect of training, organizational  climate  and work  environment  on employee  work  performance. With the total sampling technique, the sample in this study was 48 people. The results   showed;   Partial   training   has   a  positive   effect   on   employee   work performance of 4,828; Organizational climate partially has a positive influence on employee  work  performance  of  3.467;  The  work  environment  partially  has  a positive   influence   on   employee   work   performance    of   3,311;   Training, organizational climate and work environment simultaneously have a positive and significant influence on employee work performance of 37.865.